Indices for assessing road safety levels in the regions of Russia - Irina E. Ilyina; Evgeny E. Vitvitsky (Вестник СибАДИ)
Introduction. The current problem of road safety state (RTS), which appears mainly in the deterioration of the demographic situation in the Russian Federation (RF), results in the need for a significant strengthening of state activities in increasing the level of road safety. To assess the level of road safety, a system of indicators is used based on the analysis of the number of road accidents with traffic flow density, motorization level, the number of people, etc. taken into account. 80 per cent of road accidents occur in populated areas, the vast majority of them taking place in the subjects of Russian regions. At the same time, about 90 per cent of accidents occur due to violation of traffic rules by drivers, 10 per cent – by pedestrians. Today, among 89 regions of the Russian Federation, there is significant heterogeneity, determined by a number of indicators related to the territorial location, economic, social and climatic conditions that affect certain human actions (human factor) as related to a participant in street and road traffic.The purpose of the study is to determine indices for comparing cities in the road safety rating.Materials and methods. The methodological basis of the research is mathematical and statistical assessment methods.Results and discussion. The main result has been determination of parameters affecting the state of road safety. Eight indices have been grouped that characterize the level of road safety taking into account parameters of the human factor. A most important road safety parameter has been established, by considering the human factor in the “man – car – road – environment” system.Conclusion. A new methodology for assessing the level of road safety in urban environment is proposed. Identifying the subjects of the Russian Federation is most appropriate for making priority management decisions aimed at improving road safety, taking into account the human factor. The methodology will make it possible to assess the effectiveness of solving key tasks related to the prevention of road accidents, the implementation of federal targeted programs and strategies in the field of road safety in the regions of Russia.